2000
DOI: 10.1097/00008571-200003000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Association between functional genetic polymorphisms of human sulfotransferases 1A1 and 1A2

Abstract: Three human phenol sulfotransferases, provisionally named SULT1A1, 1A2 and 1A3, show 91-96% homology of their amino acid sequences and are encoded by neighbouring gene loci. Functional genetic polymorphisms are known for two of these sulfotransferases. In SULT1A1, a G to A transition leads to an Arg213 to His exchange and eliminates a Bsp143II restriction site. SULT1A1*His shows lower enzyme activity and thermostability than SULT1A1*Arg. In SULT1A2, an A to C transversion causes an Asn235 to Thr exchange and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 21 publications
5
33
2
1
Order By: Relevance
“…In addition, the observed genotype frequencies for SULT1A1 are in line with previous studies from Germany. 18,43 In summary, we observed an increased risk for colorectal cancer associated with long-term cigarette smoking and frequent consumption of red and processed meat. Our findings suggest a modifying effect of SULT1A1 genotype on the association between environmental exposures and colorectal cancer risk, which was more pronounced for red meat consumption than for tobacco smoking.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the observed genotype frequencies for SULT1A1 are in line with previous studies from Germany. 18,43 In summary, we observed an increased risk for colorectal cancer associated with long-term cigarette smoking and frequent consumption of red and processed meat. Our findings suggest a modifying effect of SULT1A1 genotype on the association between environmental exposures and colorectal cancer risk, which was more pronounced for red meat consumption than for tobacco smoking.…”
Section: Discussionmentioning
confidence: 67%
“…4 The gene SULT1A2 is usually in linkage disequilibrium with SULT1A1, and high-activity alloenzymes (SULT1A1*Arg and SULT1A2* Asn) are associated together. 5 SULT1A1*His has been associated to a protective effect in colorectal cancer, 6 although other studies have not confirmed this finding. [7][8][9][10] We have tested the main hypothesis that polymorphisms in SULT1A1 and SULT1A2 modify the risk of colorectal cancer.…”
Section: Dear Sirmentioning
confidence: 97%
“…The most common single nucleotide polymorphism is SULT1A1*2 which has a nucleotide change of G to A that causes a change from arginine to histidine at codon 213. This allozyme has lower enzymic activity and thermostability than the wild-type enzyme (Raftogianis et al, 1997;Engelke et al, 2000). An association between genetic polymorphisms of SULT1A1 and cancer susceptibility has been reported (Dalhoff et al, 2005).…”
Section: (Ix) Genetic Variability Of Sulfotransferasementioning
confidence: 99%